The Emotional Lockdown: How Social Distancing and Mask Wearing Influence Mood and Emotion Recognition in Adolescents and Adults - Kulke, Louisa; Langer, Theresia; Valuch, Christian (Frontiers in Psychology, 2022)
During the COVID-19 pandemic, government-mandated protection measures such as contact restrictions and mask wearing significantly affected social interactions. In the current preregistered studies we hypothesized that such measures could influence self-reported mood in adults and in adolescents between 12 and 13 years of age, who are in a critical phase of social development. We found that mood was positively related to face-to-face but not to virtual interactions in adults and that virtual interactions were associated with negative mood in adolescents. This suggests that contact restrictions leading to a decrease in face-to-face compared to virtual interactions may be related to negative mood. To understand if prolonged exposure to people wearing masks during the pandemic might be related to increased sensitivity for subtle visual cues to others’ emotions from the eye region of the face, we also presented both age groups with the same standardized emotion recognition test. We found slightly better performance in emotion recognition from the eyes in our student sample tested during the pandemic relative to a comparable sample tested prior to the pandemic although these differences were restricted to female participants. Adolescents were also better at classifying emotions from the eyes in the current study than in a pre-pandemic sample, with no gender effects occurring in this age group. In conclusion, while social distancing might have detrimental effects on self-reported mood, the ability to recognize others’ emotions from subtle visual cues around the eye region remained comparable or might have even improved during the COVID-19 pandemic.